Interactive Effects of Enalapril Administration and Novel HIIT Wheel-Bed Training in Aged Rats - Yang, Youfeng; Banerjee, Anisha; Sun, Yi; Carter, Christy S.; Buford, Thomas W. (Frontiers in Rehabilitation Sciences, 2021)
Growing research suggests that aerobic high-intensity interval training (HIIT) improves cardiovascular function and physical performance compared with moderate intensity continuous training (MICT). However relatively few animal models of HIIT are available to inform about the benefits of this exercise – particularly among older animals. In addition, there is little evidence for how HIIT training interacts with adjuvant pharmacological therapies known to enhance the impact of MCIT in older individuals such as Angiotensin Converting Enzyme (ACE) Inhibitors. Purpose: The aim of the present study was to establish a HIIT protocol in aged rats based on forced running wheel-bed, and to subsequently 1) establish the feasibility of the HIIT protocol in a proof-of-concept study evaluating interactions between HIIT and 2) the result of combining HIIT + ACE inhibitor treatment using the ACE inhibitor enalapril. Methods: Two groups of rats were used in this study. The feasibility of using wheel-bed for HIIT training was tested in group one (15- and 30-month-old male rats). In the second group, thirty-seven 24-month-old Fisher 344 x Brown Norway male rats were randomly divided into four subgroups: control, enalapril, HIIT training group, and HIIT training combined with enalapril administration. The training and administration lasted for 4 weeks. After the intervention, locomotor activity, exercise tolerance, and grip strength were tested. Results: Our feasibility study suggested that middle-aged and aged rats were able to successfully complete the HIIT training. In our intervention study, HIIT training alone, regardless of adjuvant enalapril intervention, did raise treadmill exercise tolerance vs. the sedentary condition. Measures of healthspan were not negatively impacted by HIIT training. Conclusion: The novel HIIT protocol based on forced running wheel-bed was successfully employed in aged rats. We conclude that future studies should compare the results and of multi-modal intervention strategies which include both HIIT and MICT in combination with adjuvant therapies such as enalapril to improve exercise tolerance and other global indices of healthspan.